PENGARUH MODEL PICTORIAL RIDDLE BERBANTUAN APLIKASI CANVA TERHADAP MINAT DAN HASIL BELAJAR PADA MATA PELAJARAN IPAS KELAS V SDN 10 SINGKAWANG - Prameswari, Dina Putri Ratih; Marhayani, Dina Anika; Setyowati, Rini (Journal of Educational Review and Research, 2024)
This study aims to 1) Is there a difference in student learning interest between the experimental class and the control class in the subject of science in class V of SDN 10 Singkawang; 2) Is there a difference in student learning outcomes between the experimental class and the control class in the subject of science in class V of SDN 10 Singkawang; 3) How much influence does the Pictorial riddle model have on students' interest and learning outcomes in the subject of science in class V of SDN 10 Singkawang. This type of research is quantitative research with a quasi-experimental design research method, in the form of a post-test only control group design. The population is all students of class V of SDN 10 Singkawang, totaling 59 students. The sample was taken using a purposive sampling technique. The data collection technique used a questionnaire sheet of learning interest and a test sheet of learning outcomes. The data analysis technique was a normality test, a homogeneity test, a two-sample t-test, and an effect size test. The results of the analysis showed that the data were normally distributed. The results of the study showed 1) After being calculated using a two-sample t-test, it was obtained that tcount> ttable, namely 3.79> 2.00, so Ha was accepted and Ho was rejected. 2) After being calculated using a two-sample t-test, it was obtained that tcount> ttable, namely 3.19> 2.00, so Ha was accepted and Ho was rejected. 3) The results of the effect size test for students' learning interest were 0.80 with high criteria, and for students' learning outcomes were 2.426 with high criteria, so it can be concluded that there is an influence of the use of the pictorial riddle model assisted by the Canva application on students' interest and learning outcomes in the subject of science in grade V of SDN 10 Singkawang